1983
DOI: 10.1063/1.332372
|View full text |Cite
|
Sign up to set email alerts
|

Coherence effects in synchronously pumped mode-locked dye lasers

Abstract: A formalism is developed for describing the evolution of picosecond mode-locked pulses in synchronously pumped dye lasers. The finite phase memory of the molecular wave functions is included, and it is found that the resultant coherence effects can be dominant for operation close to exact synchrony. Considerations of the isotropic molecular orientational distribution and the finite vibrational relaxation times are also essential in obtaining quantitative agreement with experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…The appearance of multiple pulses can be explained by the rather long time it takes to build up the gain after the pump pulse because the carriers need to relax into the quantum wells. Hence, the effective pumping time is rather long and in that limit multiple pulsing is a well known phenomenon in dye and color center lasers [11,[14][15]. They can be explained by the fact that the gain is not completely saturated by the main pulse and due to the ongoing pumping the threshold might be crossed a second time (or even repeatedly).…”
Section: Multiple Pulsingmentioning
confidence: 99%
“…The appearance of multiple pulses can be explained by the rather long time it takes to build up the gain after the pump pulse because the carriers need to relax into the quantum wells. Hence, the effective pumping time is rather long and in that limit multiple pulsing is a well known phenomenon in dye and color center lasers [11,[14][15]. They can be explained by the fact that the gain is not completely saturated by the main pulse and due to the ongoing pumping the threshold might be crossed a second time (or even repeatedly).…”
Section: Multiple Pulsingmentioning
confidence: 99%
“…Our starting point is the semiclassical dye-laser amplifier model developed in Ref. 24. Beginning with the density matrix equations and Maxwell's equations, that paper de-rived a set of ordinary, nonlinear differential equations that govern the interplay of the electric field with the molecular populations and the polarization.…”
Section: Theorymentioning
confidence: 99%
“…The dynamical rate constant associated with the field is composed of the cavity length L, the cavity lifetime t,, and the optical length mismatch AL between the pump-laser Orientational effects also manifest themselves in the specific output pulse shape, particularly at small AL's. 24 Of specific interest in this paper is the normalized pump function P(t), and for most of this work a Gaussian shape was chosen:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…shown that the inclusion o£ x is necessary £or a rigorous analysis and £or better agreement with the experiment [20]. For unidirectional distribution we can assume• X = 1 (30) The limit o£ Ts = 0, represents the rate equations …”
Section: <29)mentioning
confidence: 99%